ANALISIS PERPUTARAN PIUTANG, MODAL KERJA DAN LIKUIDITAS PERUSAHAAN DAGANG UD. DD CATERING - Yuliana, Choeriyah (EKONOMIA, 2013)
The purpose of this study are to determine the turnover of receivables, working capital and liquidity      in UD. DD Catering at Sangatta in 2011 and 2012. The experiment was conducted for 3 Months (April to June 2013) on UD. DD Catering Sangatta, related to internal control of accounts receivable. Research activities includes: literature study, field observations, interviews, documentation, data collection and analysis. Data collected in the study include: general description of the company, organization structure and respondents answers. The analytical tool used techniques / comparative descriptive analysis is to calculate accounts receivable turnover, working capital and liquidity from 2011 to 2012 using the accounts receivable turnover ratio, liquidity ratio and working capital efficiency based on data obtained in the financial statements UD. DD Catering Sengata.Results of analysis concluded that when seen from the liquidity ratio from 2011 to 2012 using the current ratio has increased 83% and the ratio of cash has increased 64% this is due to an increase in current assets and current liabilities are stable. And when seen from the ratio of working capital efficiency epidemic in 2011 and 2012 for the accounts receivable turnover has increased 41% and for working capital increased 5% this was due to a steady current in current liabities and an increase in sales and receivable